HUBUNGAN LAMA DUDUK DENGAN NECK PAIN PADA KARYAWAN PT. INSANI MEDICAL CENTER - Akmal Fribianto (2022)
Background: The use of computers in the current era of globalization in offices can causes musculoskeletal problems related to the use of computers in a sitting position for a long time and thus causes musculoskeletal problems, especially neck pain. Factors that can trigger neck pain are demographic factors including (age, gender, genetics), individual factors (Body Mass Index, smoking, psychosocial), and organizational factors (duration of work, ability to operate computers, and poor sitting posture). correct). In Indonesia, where research has been carried out on 528 office worker, this results will show us that the worker experience neck pain complaints by 52.5% with each sitting duration. Research Objectives: To determine the relations hip between long sitting and neck pain in employees of PT. Human Medical Center. Methods: The research using a cross-sectional study methode with 50 respondents through questionnaire. The variables which is used in this study were the length of sitting as independent variable and neck pain as dependent variable. Result: based from my results with SPSS 24 test, the correlation coefficient Pearson showed a significant value of 0.280 for this relationship between long sitting and neck pain. Conclusion: From the results of the analysis of this study, it founded that there was no relationship between long sitting and neck pain in employees of PT. Human Medical Center.